TINJAUAN YURIDIS MENGENAI WANPRESTASI DALAM PERJANJIAN KERJASAMA (STUDI DENGAN SEKJEN & BK DPR RI DENGAN PT. FIRST MEDIA NEWS) - Ramadhanto, Rizqi Fakhir; Sucondro, Bambang (Tribuere, 2023)
The development of communication and information technology has given birth to an information society whose demands for the right to know and the right to obtain information are increasingly greater. Broadcasting as a distributor of information and shaper of public opinion has a very strategic role, especially in developing democracy in Indonesia. This made the Secretariat General of the DPR RI as a supporting system for the DPR RI enter into a cooperation agreement with PT. First Media News to broadcast Parliament TV productions on First Media and Big TV. However, in its implementation there was a breach of contract by PT. First Media News in broadcasting Parliament TV productions. This writing uses normative juridical research methods. The legal consequences that should be carried out on PT. First Media, based on Article 7 letter b in conjunction with Article 10 of the Cooperation Agreement, will be subject to sanctions in the form of unilateral cancellation of the Cooperation Agreement by the Secretariat General of the DPR RI. The dispute can be resolved through deliberation first and if this is not successful, the dispute can be resolved through a litigation or non-litigation process. Implementation of dispute resolution regarding defaults in the Cooperation Agreement is not carried out as it should. The Secretary General of the DPR RI does not consider the default that occurred to be a problem. This is at the expense of the public being socialized about the DPR RI's activities in carrying out its constitutional duties and functions to the wider community. Based on this, it is necessary for the parties to understand the entire contents of the agreement, especially the philosophy or meaning of article by article.